Cutting Process Expert System: MOS – Machining Optimizer System - Coppini, Nivaldo Lemos; Baptista, Elesandro Antonio (Revista Ciências Exatas, 2008)
Cutting process optimization could be considered in different levels and approaches. How to select tools and how to take care about evident loose time and costs can not be considered as a competitiveness market factor any more. Everyone responsible for cutting process planning must be up to date with these procedures and the tool makers are ready to help their costumers. Otherwise, after the best selected tool and cutting conditions are settled and the process is running in shop floor many things could be done to go more deep in the cutting process optimization. One of them is how to consider the cutting process system and scenario influence on cutting condition, more specifically, on the cutting speed, which is usually select from data published in catalogues and normally based on the pair tool/workpiece. The purpose of this paper is to present a WEB based system to rich the most reliable cutting condition determination in shop floor and in real time. This system will be discussed under different scenarios (mass production and flexible production) and different cutting process (turning, milling, drilling).